The role of team and sport social contexts: Are three-level models needed in studies of sport conduct?. (March 2021) - Yukhymenko-Lescroart, Mariya A.
Abstract: In this work, I examined how variation in sport conduct is allocated across the three different levels (i.e., athlete, team, and sport) in order to consider how the team and sport environment might contribute to athletes' sport conduct. Specifically, three-level models were utilized for sportspersonship, technical and mental gamesmanship, and instrumental aggression to examine whether there is unique variance due to sport and team clustering with athletes ( N = 1412) nested within teams ( J = 92) that are in turn nested within sports ( K = 17). Results showed that clustering due to sport accounted for unique variance above and beyond team clustering. However, sex and invasion team sport explained most of the sport-level variance. The implication is that it is important to account for the sport clustering. However, when accounting for the sport-level clustering is not feasible, controlling for sex is necessary at the very least. Highlights: Findings confirmed the nested nature of the sport conduct data. Clustering due to sport accounted for unique variance beyond team clustering. Sex and invasion team sport explained most of the sport-level variance. When accounting for sport clustering is not viable, controlling for sex is needed.